2001
DOI: 10.1002/1521-3757(20011203)113:23<4549::aid-ange4549>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

From Cyclodextrin Assemblies to Porous Materials by Silica Templating

Abstract: Since the discovery by Beck, Vartuli et al. [1,2] that ordered mesoporous silicas, such as MCM-41, can be obtained by surfactant templating, the development of new porous materials and porogens as well as the characterization of the resulting structures has become one of the most promising fields in modern materials chemistry. [3±5] Meanwhile, these observations have been extended to a number of techniques by which pore morphology, pore size, and wall material can be varied over a broad range. [6±14] One of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 42 publications
3
64
0
3
Order By: Relevance
“…Just by heating, dehydration occurs, which results in the formation of carbon. Together with the recent observation that cyclodextrins (CDs), cyclic oligo-saccharides containing 6, 7, or 8 sugar units, can be employed as templates for the formation of porous silica materials with a bicontinuous and ªworm-typeº pore system, [26,28] this results in the possibility of a one-step synthesis towards the desired carbon±silica nanocomposites by high-temperature treatment under non-oxidative conditions as monoliths or continuous coatings.…”
Section: Resultsmentioning
confidence: 99%
“…Just by heating, dehydration occurs, which results in the formation of carbon. Together with the recent observation that cyclodextrins (CDs), cyclic oligo-saccharides containing 6, 7, or 8 sugar units, can be employed as templates for the formation of porous silica materials with a bicontinuous and ªworm-typeº pore system, [26,28] this results in the possibility of a one-step synthesis towards the desired carbon±silica nanocomposites by high-temperature treatment under non-oxidative conditions as monoliths or continuous coatings.…”
Section: Resultsmentioning
confidence: 99%
“…In CD solutions, dynamic light scattering (DLS) [31,32] and transmission electron microscopy (TEM) [32] have provided reliable evidence of the aggregation phenomenon. The latter has been recognized by several research groups that identified aggregates of different shapes, including spherical and elongated particles, welded fibers, and rods [1,2,19,29].…”
Section: Cyclodextrin -A Versatile Ingredient 46mentioning
confidence: 79%
“…The extensive development of CD-based formulations has resulted in a strongly increasing amount of studies, in which the exceptional features of CDs have been described (see e.g., [10][11][12][13][14][15][16]). In the last decades, CDs have also been used for functionalization of organic [17] and inorganic [18,19] materials and for the synthesis of nanosized and microsized aggregates [20][21][22]. This process is, in general, driven by hydrophobic interactions and is affected by a number Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…tion of formerly unknown structural details, [5] or to learn about the self-assembly of different cyclodextrin species to worm-like stacks in aqueous solutions. [6] Therefore, nanocasting has turned out to be a valuable analytical technique to learn about the structure of complex interacting polymer systems or colloids in water. Its main advantage is the possibility to analyze a delicate and fragile, not cuttable and badly contrasted complex fluid by its solidified and therefore permanent, well-contrasted and cuttable "hard-copy".…”
Section: Introductionmentioning
confidence: 99%